The Augmentation of Digital Violence during COVID-19: Incel Culture, Anon-IB, and Ideological Extremism (Papers in Arts and Humanities, 2021)
The abrupt onset of the COVID -19 pandemic brought devastating consequences to society as we know it. Connected to the obvious medical, societal, and economic changes, the pandemic also ushered in a world of isolation. Within this world, both media and violence are connected to imposed quarantine and confinement. During the pandemic, many studies indicated the rise of gender-based violence. For example, Mittal and Singh (2020) study the rise of quarantine violence in India. Equally disturbing is the rise of gender-based violence in digital spaces. Anon-IB is an image-based discussion board where anonymous images are posted. However, the board has become a hotbed for revenge porn and incel activity. Dutch police shut the site down in April 2018 (Vaas, 2018), but during the pandemic Anon-IB was able to find loopholes to restart itself. Users can also post headshots of a woman on the site and then ask for “wins,” which translates into nude photos. Anon-IB is location-based, and users often ask for photos of women in the surrounding area. The site also reaches aninternational audience. One example is a past thread from The University of Georgia in Tbilisi, Georgia. This paper discusses the rise of extreme online violence and revenge porn during the pandemic through a discourse analysis of Anon-IB. A discussion of incel culture will also be discussed, using the work of O’Malley et al. (2020) and others as a framework to discuss the internet’s role in ideological extremism and violence.
Keywords: COVID-19; violence; gender; incels; Anon-IB